Effects Of Different Cooking Methods And Storage Conditions On The Rice Starch Digestibility - Ramakrishnan, Yogeshini (2009)

(untitled)
Seven types of rice with different levels of amylose were selected to study the effect of different cooking methods, chilling and freezing on the digestibility of their starches. An in vitro enzymatic starch digestion method was applied in order to estimate the expected glycemic index (GI) in vivo based on the kinetics of starch hydrolysis in vitro. First, samples were cooked with different cooking methods to investigate the effect of cooking on the starch digestibility; second, samples were steamed and stored at temperatures of 4 and -20°C in order to simulate certain storage conditions of cooked rice. The results indicated significant differences in terms of starch digestibility or GI of the seven types of rice studied and the digestibility of their starches were further affected by different cooking methods. These differences can be attributed to the formation of resistant starch (RS). Steaming increased the RS formation in each type of rice. Cooking the rice with excess water, combi oven and rice cooker contributed only to small changes in the formation of RS. The proximate compositions of the rice before and after cooking were similar for all cooking methods. The amylose content of rice has an obvious impact on the rice starch digestibility due to its positive correlation with formation of RS. Starch hydrolysis was found to be rapid and complete for the waxy and low amylose rice rather than for the intermediate and high amylose rice. Chilling of steamed rice promoted the formation of RS more than freezing. The GI ranged between 68 and 98 for steamed rice and between 63 and 82 for chilled and frozen rice. Storing steamed rice at 4°C and -20°C gradually increased the formation of RS and reduced the estimated GI for all the seven types of rice. A high decrease in starch hydrolysis after chilling and freezing was found among the waxy rice. Thermal properties of rice that have undergone steaming, chilling and freezing showed a shift of the gelatinization temperature to a higher value. The pasting properties of steamed and chilled or frozen rice samples showed increased pasting temperatures and decreased peak viscosity compared to those of raw rice. The raw rice starches had the characteristic A-type crystalline pattern, with diffraction peaks at 15.2, 17.2, 17.9 and 23.2° (2θ). The steaming, chilling and freezing treatment on rice caused weak peak formation at 16° and 20° (2θ) representing crystalline B-type and V-amyloselipid complexes. Steaming, chilling and freezing of rice had reduced the relative crystallinity (RC) value.